A single-center experience of non-bioartificial liver support systems among Chinese patients with liver failure. Issue 6 (June 2014) - Xia, Qi; Dai, Xiahong; Huang, Jianrong; Xu, Xiaowei; Yang, Qian; Liu, Xiaoli; Chen, Yuemei; Li, Lanjuan
Introduction: Liver failure is one of the most deadly, prevalent, and costly diseases worldwide. Non-bioartificial liver support systems (NBALs) have been shown to be effective in improving the clinical symptoms and laboratory parameters of patients with liver failure. The main aim of this large case series analysis was to investigate the status of NBALs and their effectiveness in improving survival in liver-failure patients. Methods: In this retrospective study, 460 patients with liver failure who received NBAL treatment in addition to conventional medications were compared with 422 patients who were treated with conventional medications alone. Kaplan-Meier and life table analyses were used to estimate survival rates. Results: Clinical outcomes were improved after NBAL treatment. The 30-day survival rates of subacute liver failure (SALF) patients were 63% among those who received NBALs and 21% among those who did not receive NBALs (p<0.01). Similarly, the 30-day survival rate of acute-on-chronic liver failure (ACLF) patients who received NBALs was 47%, significantly higher than that of the non-NBAL patients (p<0.05). The survival rates of ACLF patients with low Model for End-Stage Liver Disease (MELD) scores (MELD≤20) were 64% and 40% among whom received NBALs and those who did not, respectively (p<0.01). Conclusions: NBAL treatment is helpful to improve the survival of patients with ALF, SALF or ACLF. ACLF patients with lower MELD scores showed improved outcomes relative to those with higher MELD scores.